Green Synthesis of SnO2 Nanocrystals Using Garcinia Mangostana L Fruit Peels Extract as Natural Capping Agent - Asdim Asdim; Alim Rijali; Qurnia Susanti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2024)
The hydrothermal synthesis of SnO2 nanocrystals at a relatively low-temperature range of 95-100 °C was successfully conducted utilising Garcinia Mangostana L fruit peel extract as a natural capping agent. Characterisation of the synthesised SnO2 nanocrystals was performed using an X-ray diffractometer (XRD) for phase analysis and determination of crystallite size and a Scanning Electron Microscope (SEM) for morphology analysis. XRD analysis revealed the formation of phase-pure SnO2 nanocrystals, with distinct peaks at angles (2θ) of 26.01°, 33.89°, and 51.70° corresponding to miller indices (110), (101), and (211) as per JSPDS standard data. The absence of impurity peaks in the XRD pattern indicated the high purity of the synthesised SnO2 nanocrystals. SEM images exhibited differences in the size and morphology of the synthesised SnO2 nanocrystals with and without the extract. Specifically, the presence of the fruit peel extract led to a reduction in aggregate formation and inhibited crystal growth, resulting in smaller aggregates. These findings highlight the significant impact of Garcinia Mangostana L fruit peel extract on the hydrothermal synthesis of SnO2 nanocrystals with varied sizes and morphologies.